A case of necrotizing fasciitis from a pedicure: when beauty centers become life-threatening - Pozzi, Mirco; Cuomo, Roberto; Giardino, Francesco Ruben; Brandi, Cesare; Nisi, Giuseppe; Grimaldi, Luca (Acta Biomedica Atenei Parmensis, 2022)
Introduction: in a historical moment where there is an increasing use of beauty center, we report a case of necrotizing fasciitis occurred after a pedicure, with the aim of clarifying the safety of these aesthetic treatments. Case report: we discuss a case of left foot necrotizing fasciitis as consequence of removing a plantar callus. The patient is a 49 years old man; he is hypertensive, and diabetic not controlled. We report our experience showing the clinical manifestation and the tricky profile of the patient; then we reflect on the safety profiles of these aesthetic treatments. Discussion: some bacterial infections of soft tissue after pedicure and manicure are reported in Literature. Mycobacteria seems to play a prevalent role, mostly after a peculiar practice of “fish pedicure”. Our experience shows how the combination between a patient with complicated profile and poor hygienic measures can have catastrophic consequences. Conclusion: the aim of this article is to raise awareness on the serious consequences that can arise from banal aesthetic procedures. Furthermore, we want to recommend more control over these treatments performed in Beauty Salon, considering the large turnout of people, even clinically sensitive.